The role of self-regulation in corporate governance: evidence and implications from The Netherlands - de Jong, Abe; DeJong, Douglas V.; Mertens, Gerard; Wasley, Charles E. (Journal of Corporate Finance, 2005)
This paper studies The Netherlands' private sector self-regulation initiative (“The Peters Committee”) to improve corporate governance practices. We examine the relation between firm value and corporate governance characteristics before and after the private sector initiative. We find the initiative had no effect on corporate governance characteristics or their relationship with firm value. Event study results suggest the market was skeptical about the success of self-regulation of corporate governance practices in The Netherlands. Our results on The Netherlands self-regulation initiative suggest little should be expected from initiatives that rely on monitoring without enforcement (e.g., similar or weaker initiatives in other European Union (EU) countries).